TECHNOLOGICAL EDUCATION IN THE MATHEMATICAL EDUCATION FRAMEWORK: ARTICULATING UNDERSTANDINGS - Mondini, Fabiane [UNESP]; Mocrosky, Luciane Ferreira [UNESP]; Orlowski, Nelem; Simões, Alexandre da Silva [UNESP] (My University, 2021)
In this article, we expose understandings for technological education, or technological mathematical education, following the path of explaining how we have come to understand what has been supporting school mathematics. To do this, we focus on mathematical predictability and accuracy, which are often required in educational processes, articulating it with the formation of people and bringing in it computational thinking as a creative way of linking science-technology-mathematics-teaching. We conclude that technology sustains a structural change in our society, in the way we live and act, in the way we teach and learn. This change also extends to the educational scenario in which Technological Education emerges, as a forming movement, which is structured based on technology, but beyond utility, bringing temporality, guided by the sense it makes in the world and calling us to think, in this context, Technological Education in the scope of Mathematical Education, as a formative possibility.
EDUCAÇÃO TECNOLÓGICA NO ÂMBITO DA EDUCAÇÃO MATEMÁTICA: ARTICULANDO COMPREENSÕES
Keywords: Computational Thinking; Mathematical Education; People formation; Technological Education